Image Processing and CFD Simulation Method Comparison in Determining and Visualizing Fluid Flow of a Marine UAV - Sinung Widiyanto; G. A. P. Poundra; Tri Agung Kristiyono; Widyawasta; Sayuti Syamsuar (Institut Teknologi Sepuluh Nopember, 2023)
An investigation of marine UAV performance with various designs have done successfully. The analysis was based on resistance criteria identification both aerodynamically and hydrodynamic. The calculations were conducted with the assistance of image processing as the experimental attempt and High-Fidelity Computational Fluid Dynamics (CFD) software code to simulate the fluid flow on the fuselage designs, pontoons, and image processing. Both methods compared to acquire the silver line in which way they can collaborate to create new way of testing. Furthermore, mathematical calculations and Image processing works refereeing were also performed as the attempt for validations and conclusion.